Indegenous Knowledge Of Upland Tree Management: A Case Study Of The Khasi Of Northeast Bangladesh - Majumder, Nur Mohammad (2017)
This study is on indigenous knowledge of upland tree management of Khasi community in Sylhet, northeast Bangladesh. It explored how Khasi people use indigenous knowledge for the management of fruit-bearing trees and also how the farmers hybridize traditional and modern farming elements in the management of fruit bearing trees, the study also examined the various farming threats and challenges encountered by the farmers in carrying-out the tree management activities. Two villages were selected in this study; qualitative method guided this study with a total sample size of 76 respondents.